AL-THÛFÎ : REPRESENTASI KAUM LIBERALIS TERHADAP PEMBENTUKAN HUKUM ISLAM - Moh Mufid (Istinbath : Jurnal Hukum, 2016)
The dynamics of Islamic legal thought continue rolling relentlessly. One of the frequently asked questions discourse in academic circles is about the concept of affairs. The most controversial are considered related that concept was Najm al-Din al-Thûfî. In his work, al-Thûfî seek elaborating the thought of his predecessors. The thought of al-Thûfî that's cause he is regarded as a liberal figure, for daring to "against" nash. One of the points from the al-Thûfî of affairs is that Affairs is the most powerful sharee'ah (al-mashlahah al-syar'i adillat Sukhumi). For al-Thûfî, when nash and consensus contrary to Affairs, should take precedence by way of takhshish Affairs and bayan against nash. This then gave birth to the pros and cons against the thought of al-Thûfî. On the other hand, thanks to the brilliant thought, then al-Thûfî often referred to as the House of Liberals. Whereas there is a fundamental difference related to the thought of al-Thûfî with the Liberals in Indonesia.